Vulnerabilidad social de las personas con analfabetismo funcional de la Parroquia Santa Teresita, Cantón Espíndola, periodo 2018 - GAONA GUARNIZO, MARIA BELEN (2019)
Education is of vital importance since it allows us to function correctly within society. (UNESCO, 2017) has determined that there is a considerable number of people who suffer from functional illiteracy in Ecuador, which limits the possibilities of life and increases the vulnerability of the country. In Ecuador, various government plans and projects have been implemented with the aim of eradicating functional illiteracy, although there are areas that have this problem, such as the Santa Teresita parish. This is a topical issue because all governments have set out to eradicate or reduce illiteracy, but it has always been impossible, no matter how much effort and investment is made. Social vulnerability in people with functional illiteracy is a social problem in which we are all involved since it slows down the progress of the country and the quality of life of its inhabitants. In order to know the percentage of people with this condition, a survey was carried out with 262 inhabitants of the Santa Teresita parish and thanks to the first question, it was possible to determine the level of education of the people surveyed, since according to UNESCO, a person in a condition of functional illiteracy is considered a person who has completed 3 years or less of primary education, resulting in a total of 71 people with this condition. The first is to characterize the population in a situation of functional illiteracy in order to determine which population is the most vulnerable within the parish of Santa Teresita. For this purpose, the results of the survey were analyzed by fragmenting them 5 through gender and age variables, resulting in the most vulnerable people being women of adult age. The second specific objective, to establish the degree of social vulnerability of the population with functional illiteracy of the parish of Santa Teresita, in order to comply with it, an analysis and adjustment of Laura Golovanevsky's measurement proposal was carried out, which is defined as the sum of four components: education, health, housing and work. Prior to the last activity mentioned, the population was classified into 3 groups according to their level of education; therefore, people in a functional illiteracy condition have a medium-high degree of social vulnerability, people without this condition have a low degree of vulnerability and people in a pure functional illiteracy condition have a medium degree of vulnerability. The third objective made it possible to propose social policy guidelines to improve the situation of social vulnerability of people with functional illiteracy in the parish of Santa Teresita, and for this purpose the various bibliographical sources were analyzed in order to learn more about the subject and to comply with its development.